BAG3 induces fibroblasts to release key cytokines involved in pancreatic cell migration. Issue 1 (6th November 2021) - Dufrusine, Beatrice; Damiani, Verena; Capone, Emily; Pieragostino, Damiana; Dainese, Enrico; De Marco, Margot; Reppucci, Francesca; Turco, Maria C.; Rosati, Alessandra; Marzullo, Liberato; Sala, Gianluca; Sallese, Michele; et al.
Abstract: Pancreatic ductal adenoma carcinoma (PDAC) is considered one of the deadliest solid cancers as it is usually diagnosed in advanced stages and has a poor response to treatment. The enormous effort made in the last 2 decades in the oncology field has not led to significant progress in improving early diagnosis or therapy for PDAC. The stroma of PDAC plays an active role in tumour initiation and progression and includes immune cells and stromal cells. We previously reported that Bcl2‐associated athanogene (BAG3) secreted by PDAC cells activates tumour‐associated macrophages to promote tumour growth. The disruption of this tumour–stroma axis by the anti‐BAG3 H2L4 therapeutic antibody is sufficient to delay tumour growth and limit metastatic spreading in different PDAC preclinical models. In the present study, we examined the role of BAG3 to activate human fibroblasts (HF) in releasing cytokines capable of supporting tumour progression. Treatment of fibroblasts with recombinant BAG3 induced important changes in the organisation of the cytoskeleton of these cells and stimulated the production of interleukin‐6, monocyte chemoattractant protein‐1/C–C motif chemokine ligand 2, and hepatocyte growth factor. Specifically, we observed that BAG3 triggered a depolymerisation of microtubules at the periphery of the cell while they were conserved in the perinuclear area. Conversely, the vimentin‐based intermediate filaments increased and spread to the edges of the cells. Finally, the conditioned medium (CM) collected from BAG3‐treated HF promoted the survival, proliferation, and migration of the PDAC cells. Blocking of the PDAC‐fibroblast axis by the H2L4 therapeutic anti‐BAG3 antibody, resulted in inhibition of cytokine release and, consequently, the inhibition of the migratory phenotype conferred by the CM to PDAC cells.